A retrospective longitudinal evaluation of new overactive bladder patients in an FPMRS urologist practice: Are patients following up and utilizing third‐line therapies?. Issue 1 (16th November 2020) - Du, Chris; Berg, William T.; Siegal, Alexandra R.; Huang, Zhenyue; Nguyen, Anh; Cheung, Alice; Mehraban‐Far, Sina; Anderson, Rebecca; Jacob, Sophia; Kim, Jason
Abstract: Aims: Third‐line therapies are efficacious in improving overactive bladder (OAB) symptoms; however, OAB patients have poor follow‐up and rarely progress to these therapies. Clinical care pathways (CCP) may improve OAB follow‐up rates and third‐line therapy use. We sought to determine how new OAB patients follow up and utilize third‐line therapies with the implementation of an OAB CCP in a fellowship Female Pelvic Medicine and Reconstructive Surgery (FPMRS) trained urologist's academic practice. Methods: We identified new OAB patients using ICD‐9 and 10 codes. They were placed into two groups: pre‐ and post‐CCP use. Basic demographic data were collected. Patients were evaluated in a retrospective longitudinal fashion over 12 months to determine follow‐up and third‐line therapy utilization. Results: A total of 769 new OAB patients (261 pre‐CCP and 508 post‐CCP) were identified. The mean number of follow‐up visits increased significantly at 6 months (0.94 vs. 1.64 visits, p = .001) and 12 months (1.26 vs. 2.46 visits, p < .003). Follow‐up rates increased significantly at 3 months (38.7% vs. 50.2%, p = .002). Mean time to third‐line therapy decreased significantly (280 days vs. 160 days, p = .016). Third‐line therapy utilization therapy rates increased at 6 months (7.7% vs. 13.4%, p = .018) and at 12 months (11.1% vs. 16.5%, p = .044). Conclusions: New OAB patients follow‐up and progress to third‐line therapies faster and more frequently with the use of a CCP in an FPMRS‐trained urologist practice. However, many OAB patients still fail to follow up and overall utilization of third‐line therapies remains low. Future studies are warranted to identify factors to why overall OAB compliance remains low.